Inhibitive performance of gemini surfactants as corrosion inhibitors for mild steel in formic acid - Ansari F.A.; Quraishi M.A. (My University, 2025)
Three new gemini surfactants referred to as n-2-n (where n= 6, 12, 16) were developed as corrosion inhibitors for mild steel. Their critical micelle concentration (cmc) at equilibrium in water at 30°C was determined. Corrosion inhibition studies of mild steel in formic acid by gemini surfactants were conducted by using weight loss, electrochemical polarisation and electrochemical impedance spectroscopy (EIS) measurements. Scanning electron microscopic study (SEM) was also used to investigate the surface morphology of inhibited and uninhibited metal samples. The results obtained show that the surfactants studied are good mixed type inhibitors. The result was also correlated with several factors, including the chain length of the hydrophobic chains, critical micelle concentration (cmc) and adsorption free energy of these inhibitors. The adsorption of all the gemini surfactants was found to follow Langmuir adsorption isotherm. EIS results indicate that the change in the impedance parameters (Rt and Cdl) with concentration of inhibitors was due to the formation of a protective layer on the surface of mild steel.